Migrant Adult Language Learning in a Transnational Context - Ippolito, John; Rehner, Katherine (Journal of the Canadian Association for Curriculum Studies, 2020)
This presentation reports on the preliminary stages of a multi-year adult literacy project. The project is motivated by the intensity of contemporary global migration, where unprecedented numbers of adult migrants are forced into linguistically alien terrains and are often isolated and disadvantaged by language barriers preventing full participation in host societies. The project responds to this challenge with a comparative analysis of the formal and informal language learning experiences of adult migrants in three transit or destination countries characterized by an influx of newcomers: York Region, Ontario, Canada; Erie County, Pennsylvania, United States; and Agrigento, Sicily, Italy. Using a hybrid theoretical framework linking transnationalism (Glick Schiller, Basch & Szanton Blanc, 1995) and translanguaging (Otheguy, García & Reid, 2015), the project undertakes a fluid and multidirectional study of migration and conducts an analysis directed at the first-person experiences of language use in linguistically diverse contexts. Drawing on surveys and interviews, the project assesses migrants’ priorities for language learning, their agency in choosing language-learning opportunities and how language learning serves their needs. Supplementary perspectives from adult education providers and academics in migration-related fields inform evidence-based pedagogical and policy recommendations for how language-learning opportunities can support the social integration of adult migrants.